BCR SIGNALING INHIBITORS: AN OVERVIEW OF TOXICITIES ASSOCIATED WITH IBRUTINIB AND IDELALISIB IN PATIENTS WITH CHRONIC LYMPHOCYTIC LEUKEMIA - Lorenzo Falchi; Jessica M Baron; Carrie Anne Orlikowski; Alessandra Ferrajoli (Mediterranean Journal of Hematology and Infectious Diseases)
The B-cell receptor signaling inhibitors ibrutinib and idelalisib are revolutionizing the treatment landscape of chronic lymphocytic leukemia (CLL) and other B-cell malignancies. These oral agents, both alone and in combination with other drugs, have shown remarkable clinical activity in relapsed or refractory CLL across all risk groups, and have been approved by the Food and Drug Administration for this indication. Preliminary data suggest that an even greater benefit can be expected in treatment-naïve CLL patients. Both ibrutinib and idelalisib are well tolerated by most patients, including older, frailer individuals. Toxicities are usually mild and self-resolving. Clinicians must, however, be aware of a number of peculiar adverse events, the effects of which can be severe enough to limit the clinical use of these agents. In this review, we survey the salient aspects of the pharmacology of these agents, as well as clinical experience regarding their use for the treatment of patients with CLL. Our foci will be both the most common and the most clinically significant toxicities associated with these drugs.